The fate of immune complexes in membranous nephropathy - Xu, Jie; Hu, Haikun; Sun, Yuhe; Zhao, Zihan; Zhang, Danyuan; Yang, Lei; Lu, Qingyi (Frontiers in Immunology, 2024)
The most characteristic feature of membranous nephropathy (MN) is the presence of subepithelial electron dense deposits and the consequential thickening of the glomerular basement membrane. There have been great advances in the understanding of the destiny of immune complexes in MN by the benefit of experimental models represented by Heymann nephritis. Subepithelial immune complexes are formed in situ by autoantibodies targeting native autoantigens or exogenous planted antigens such as the phospholipase A2 receptor (PLA2R) and cationic BSA respectively. The nascent immune complexes would not be pathogenic until they develop into immune deposits. Podocytes are the major source of autoantigens in idiopathic membranous nephropathy. They also participate in the modulation and removal of the immune complexes to a large extent. The balance between deposition and clearance is regulated by a wide range of factors such as the composition and physicochemical properties of the immune complexes and the complement system. Complement components such as C3 and C1q have been reported to be precipitated with the deposits whereas a complement regulatory protein CR1 expressed by podocytes is involved in the phagocytosis of immune complexes by podocytes. Podocytes regulate the dynamic change of immune complexes which is disturbed in membranous nephropathy. To elucidate the precise fate of the immune complexes is essential for developing more rational and novel therapies for membranous nephropathy.